Fabrication of Split-Luciferase Complementation Assays for Molecular Imaging - Bae Kim, Sung; Ozawa, Takeaki (Current Molecular Imaging (Discontinued), 2013)
Recent revolutionary developments in luciferase engineering technologies now allow researchers to carry out quantitative imaging of molecular dynamics and cell signaling in living subjects, the technology of which includes protein-fragment complementation assay (PCA) and intein-mediated protein splicing assay (PSA). These technologies are functionally optimized with specific marine and beetle luciferases exerting designed properties and functionalities. This review overviews how to fabricate such bioluminescent tools and technologies of reconstituting split-luciferases, providing an excellent platform for today’s molecular imaging.
Keywords: protein-fragment complementation assay (PCA)